Limits and challenges of inclusive education in the countryside: the experience of the MST educational project - Santos Barcellos, Luis Henrique dos [UNESP]; Silva, Claudio Rodrigues da [UNESP]; Domingos Moraes, Agnes Lara; Torres, Julio Cesar [UNESP] (Univ Federal Tocantins, Campus Tocantinopolis, 2020)
The objective of this research was to analyze the Inclusive Education in MST guiding documents, more specifically, in its education proposal. For the development of the study, bibliographic research and documentary analysis were used. The Movement of Landless Rural Workers (MST) is the main Brazilian movement of struggle and resistance for land and against the advancement of capitalism. To defend its ideas, the MST chooses as one of the central lines the development of an emancipatory education, which combines work and education in the management of production, through democratic relations and actions. The research seeks to investigate how the Movement treats inclusion in its educational project, therefore, an approximation was established between Special and Inclusive Education, and these with Rural Education, based on the guidelines expressed in the MST pedagogical project. It was possible to verify general organizational principles, but, due to the territorial dimension of the Movement's actions, and the respect for the particularities of the actions taken in the localities, the different educational experiences of the MST may disagree, to a greater or lesser extent, with each other.
Keywords: Rural Education; Inclusive Education; Special Education; MST